Effects of cerebral gymnastics in cognition and subjective welfare of institutionalized elderly people - Carlos Eduardo Viana Santos; Alex de Oliveira Ribeiro; Luciana Crepaldi Lunkes (Editora Champagnat, 2019)
Abstract Introduction: With the increasing number of elderly people, greater care is required for this population, and zeal for health and quality of life becomes an important goal in healthy aging. Elderly people can achieve excellent results involving cognitive training based on brain plasticity. Objective: To verify the effectiveness of cerebral gymnastics in the cognitive state and well-being of institutionalized elderly women. Method: Clinical trial performed with nine institutionalized elderly women, mean age of 80.2 years old (± 9.1). The Subjective Well-being Scale and tests (clock, verbal fluency, figure recognition) were administered before and after ten weeks of the exercise program (eight exercises performed in two weekly meetings, involving figures, words and objects). The data normality was verified using the Shapiro-Wilk test, followed by Student t tests for analysis of SWB and Wilcoxon for analysis of figure recognition, clock-drawing test and verbal fluency. Results: Significant improvement in the incidental and immediate memory 1 and 2 (p = 0.007), verbal fluency (p = 0.011, p = 0.025 and p = 0.007) and the clock-drawing test (p value = 0.046). No significant results were found for SWB (p = 0.357 and p = 0.389). Conclusion: Brain gymnastics beneficially modified cognitive performance. Well-being did not show significant improvements.